The advertising practitioner and the imbuement of Al-Ghazali’s Islamic ethics framework / Aida Mokhtar. - Mokhtar, Aida (Faculty of Communication and Media Studies, Universiti Teknologi MARA, 2019)
The imbuement of Islamic ethics by advertising practitioners is central to the sculpturing of Islamic advertising messages. Ethical advertising encompasses several dimensions and of major focus here is ethics in relation to the advertising practitioner. The Muslim Islamic advertising practitioner has the role of forming advertising objectives that would succeed in achieving advertising effects on earth and in attaining eternal goodness in the Hereafter in line with Islamic ethics. The article applies four themes of a framework generated from Al-Ghazali’s Al-Ihya’ to Muslim Islamic advertising practitioners. The themes centre on the practitioners’ need for understanding the ideals of a believer while conducting business activities by embracing the key concepts of vicegerency, Tawhid, Ihsan, Islam, Iman and wasatiyyah in repelling moral myopia that underscores the practitioners’ difficulty in identifying ethical issues. The Muslim practitioner who recognises and embraces the Islamic purpose of life would use Islam as a holistic guide in life including when making decisions for advertising production.